Family carers' perspectives on post‐school transition of young people with intellectual disabilities with special reference to ethnicity. (23rd July 2012) - Raghavan, R.; Pawson, N.; Small, N.
Abstract: Background  School leavers with intellectual disabilities (ID) often face difficulties in making a smooth transition from school to college, employment or more broadly to adult life. The transition phase is traumatic for the young person with ID and their families as it often results in the loss of friendships, relationships and social networks. Method  The aim of this study was to explore the family carers' views and experiences on transition from school to college or to adult life with special reference to ethnicity. Forty‐three families (consisting of 16 White British, 24 Pakistani, 2 Bangladeshi and one Black African) were interviewed twice using a semi‐structured interview schedule. The carers were interviewed twice, Time 1 (T1) and Time 2 (T2), T2 being a year later to observe any changes during transition. Results  The findings indicate that although transition planning occurred it was relatively later in the young person's school life. Parents were often confused about the process and had limited information about future options for their son or daughter. All family carers regardless of ethnicity, reported lack of information about services and expressed a sense of being excluded. South Asian families experienced more problems related to language, information about services, culture and religion. Conclusions  The majority of families lacked knowledge and awareness of formal services and the transition process. Socio‐economic status, high levels of unemployment and caring for a child with a disability accounted for similar family experiences, regardless of ethnic background. The three key areas relevant for ethnicity are interdependence, religion and assumptions by service providers.